INTRUSIVE MARKETING METHODS A CONTEMPORARY CONSUMER PERSPECTIVE - Owais, Faizan (2008)
Is marketing practice destroying the faith of consumers? It may be argued that marketing practice over recent years has taken a more direct approach that appears intrusive and manipulative to consumers. The marketing activities we see today are a desperate attempt to grab consumer attention in any way possible and it is all spelling out bad news for marketing. Marketers have been faced with many challenges, with markets at saturation point, competitiveness is on the rise and marketers are faced with shortened product life cycles. Further, technology and new media have diminished customer attention from one specific media, which have led to increasing levels of advertising - targeting consumers online, via telephone, direct mail, email and through mobile messaging. Consumers have always found a way to distract themselves from the thousands of marketing messages thrown at them wherever they go. The collective impact of new marketing techniques is causing consumers to complain, and research suggests consumers have reached their saturation point of tolerance. This study takes a consumer perspective of how they perceive intrusive marketing practices to determine if consumers really want such treatment from marketers.